2012
DOI: 10.1016/s0313-5926(12)50019-6
|View full text |Cite
|
Sign up to set email alerts
|

Tax Morale and Tax Evasion: Social Preferences and Bounded Rationality

Abstract: We study a family of models of tax evasion, where a flat-rate tax finances only the provision of public goods, neglecting audits and wage differences. We focus on the comparison of two modeling approaches. The first is based on optimizing agents, who are endowed with social preferences, their utility being the sum of private consumption and moral utility.The second approach involves agents acting according to simple heuristics. We find that while we encounter the traditionally shaped Laffer-curve in the optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…(5) Besides tax morale, factors such as social norms, social influence, fairness concerns, and perceptions of the distributive outcomes of the tax system are increasingly considered as likely determinants of tax compliance (Alm et al, 2012;Braithwaite and Wenzel, 2008;Hofmann et al, 2008;Kirchler, 2007;Kirchler et al, 2010;Meder et al, 2012). All these contributions suggest that the standard economic approach alone is not able to account for a complex social phenomenon such as tax evasion.…”
Section: The Problem Of Tax Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…(5) Besides tax morale, factors such as social norms, social influence, fairness concerns, and perceptions of the distributive outcomes of the tax system are increasingly considered as likely determinants of tax compliance (Alm et al, 2012;Braithwaite and Wenzel, 2008;Hofmann et al, 2008;Kirchler, 2007;Kirchler et al, 2010;Meder et al, 2012). All these contributions suggest that the standard economic approach alone is not able to account for a complex social phenomenon such as tax evasion.…”
Section: The Problem Of Tax Compliancementioning
confidence: 99%
“…Traditional explanations based on deterrence were too often linked to the strict assumptions of rational choice theory and the homo oeconomicus model (Allingham & Sandmo, 1972). Instead, recent studies focus, for example, on taxpayers' tax morale (their tolerance towards tax fraud), social norms, social interaction effects, ethical values, fairness perceptions, knowledge of the tax system, or attitudes towards government and public expenditure (Alm, 2012;Alm et al, 2012;Braithwaite and Wenzel, 2008;Hofmann et al, 2008;Kirchler, 2007;Kirchler et al, 2010;Meder et al, 2012;Torgler, 2007Torgler, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that there is a causal link between aggregated tax morale and the volume of the shadow economy at the national level [36]; at the individual level, some contributions have proved the relationship between individual tax morale and self-declared levels of tax evasion [19,24,62], as well as tax noncompliance behavior in the laboratory [43]. Besides tax morale, factors such as social norms, social influence (SI), fairness concerns and perceptions of the distributive outcomes of the tax system are increasingly taken as likely determinants of tax compliance [5,20,39,41,42,50].…”
Section: Presentation and Purpose Of Simulfismentioning
confidence: 99%
“…Tax inspection models are often very different, particularly in relation to their complexity. For example, in [22][23][24][25][26][27] a number of models have been described and analysed, each with different assumptions, different levels of complexity (models that were developed earlier are simpler, and later models are more complex), different validation methods and are developed in different simulation environments. ABM has also been used in analysis of (inspection of) crime [6,28] and banking supervision [29].…”
Section: Agent-based Modelling (Abm)mentioning
confidence: 99%